(untitled) (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2026)
This article presents analyses of epistemic movements made by students in the process of solving multiplicative structure situations. Of a qualitative nature, in an interpretative approach, the data was produced with four 4th grade students from a Municipal School of Full-Time Basic Education (EMEBTI) in the municipality of Vargem Alta - ES, using audio and video recordings and students’ written records as data production tools. Based on studies on Problem Solving, Mobile Devices with Screen Touches and Embodied Cognition, the interpretation of the epistemic movements (gestures and screen touches) made by the students in the development of the story “The Mystery of the Folded Cubes”, while investigating mathematical situations of multiplication, took place through the Multimodal Schematic Representation of Data Analysis (REMAD). The analyses showed that gestural movements and touches on the screen were part of mathematical learning, revealing epistemic actions in the ways of thinking mathematically, through actions of collecting, connecting and recognizing structures. These findings reinforce that mental actions can be observed through hand movements, constituting a way of showing and materializing thought in social interaction. Translated with DeepL.com (free version)